Modelagem da cobertura do solo urbano no Vetor Norte da RMBH e projeções de cenários futuros considerando as novas infraestruturas viárias previstas - Daniel Martins Sampaio (2014)
The economic boom in recent years has been interfering in the model of urban settlement in the Metropolitan Region of Belo Horizonte (RMBH). The valuation of the Land led the real state market to push the urban occupation toward the Northern sector of the RMBH. Thus it arises a concern of how to conserve natural resources, which is a critical condition to the society's quality of life, and maintain urban growth in the region. Besides the action of the real state market, the urban expansion in the Northern sector, has taken influences from large public works planned and already implemented in the area such as, the Tancredo Neves International Airport, the Airport-Industry, the Linha Verde and Administrative Center of Minas Gerais. This study aimed to model the dynamics of groundcover in order to predicts scenarios of urban growth within the northern sector Belo Horizonte Metropolitan Region (RMBH), therefore investigate the spatial influence of the planned transportation infrastructure with a foreseen horizon for the year 2031. Using GIS techniques, remote sensing and data modeling enabled to identify the urban areas located in northwest and east of Northern Sector of RMBH were land changes were more intense. The variables employed in the model were tested and prediction model of landuse change reached 82.61% accuracy providing the elaboration of a scenario to 2011. Given a set of thirteen explanatory variables tested in the model of urban expansion, two were strong related to the potential of explanation based on the model of V de Cramer V: Areas with the occurrence of a change in groundcovers between 2001 and 2006 presenting an index of 0,3741 and the Distance from existing urban and commercial centers with an index of 0.3532. The variables employed in the model were tested and prediction model of land changes reached 82.61% accuracy providing the elaboration of a scenario to 2011. This scenario was validated based on 2011 satellite image and presented 92.60% accuracy and 7.40% of commission error. Next, three predictive scenarios were simulated for 2031. Findings pointed to a strong tendency of urban groundcover changes occur in part of the municipalities of Ribeirao das Neves, Sao Jose da Lapa, Santa Luzia and Vespasiano. As conclusion, this investigation can contribute to elaboration and application of public policies necessary for supporting urban growth.